2012
DOI: 10.1039/c2mb25239b
|View full text |Cite
|
Sign up to set email alerts
|

Ter-dependent stress response systems: novel pathways related to metal sensing, production of a nucleoside-like metabolite, and DNA-processing

Abstract: The mode of action of the bacterial ter cluster and TelA genes, implicated in natural resistance to tellurite and other xenobiotic toxic compounds, pore-forming colicins and several bacteriophages has remained enigmatic for almost two decades. Using comparative genomics, sequence-profile searches and structural analysis we present evidence that the ter gene products and their functional partners constitute previously underappreciated, chemical stress response and anti-viral defense systems of bacteria. Based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
123
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(131 citation statements)
references
References 122 publications
(309 reference statements)
8
123
0
Order By: Relevance
“…It has been suggested that tellurite resistance is a collateral effect of an oxidative stress resistance phenotype, providing pathogenic bacteria with the ability to counteract host defenses (16,18,35). Our results show that tellurite resistance is strongly associated with CG23, CG65, and CG86.…”
Section: Downloaded Fromsupporting
confidence: 65%
“…It has been suggested that tellurite resistance is a collateral effect of an oxidative stress resistance phenotype, providing pathogenic bacteria with the ability to counteract host defenses (16,18,35). Our results show that tellurite resistance is strongly associated with CG23, CG65, and CG86.…”
Section: Downloaded Fromsupporting
confidence: 65%
“…While highly toxic to bacteria, tellurite is not necessarily commonly encountered, which raises the question of why these genes exist in such a wide range of species. It has been argued that the Te r genes are part of a general stress response system rather than solely tellurite resistance (21,30,34). In support of this, the Ter genes in E. coli are also implicated in resistance to bacteriophage and colicin (35).…”
Section: Discussionmentioning
confidence: 66%
“…YceG remains poorly characterized with little sequence homology to other known tellurite resistance proteins. YceG has strong hydrophobic regions that may allow for interaction with the membrane, and across bacterial species, it is often found in association with TelA, indicating that these two proteins might be functionally linked (34). Despite their being widespread, surprisingly little is known regarding the actual function of any of the Te r genes.…”
Section: Discussionmentioning
confidence: 99%
“…Further research is necessary to understand the role of this important conserved gene in both bacteria and phages. TerC is required for tellurite resistance in E. coli, and several tellurite resistance genes are known; however, the mechanisms by which these proteins function is largely unknown (84)(85)(86). Tellurium oxyanion (TeO 3 2ÏȘ ) has been used in the treatment of mycobacterial infections, and resistance is a feature of many pathogenic bacteria (79).…”
Section: Discussionmentioning
confidence: 99%